A shape selective MOF material for the adsorptive separation of linear and branched hexane isomers - Bárcia, Patrick da Silva (2011)
Single and multicomponent fixed bed adsorption of hexane isomers were studied on a MOF Zn(BDC)(Dabco)0.5. The breakthorugh experiments show a highly selective sorption with respect to n-Hexane.